TEOREMA PAPPUS PADA ELIPS, PARABOLA DAN HIPERBOLA - Ardiansyah Yan Hakim Nasution; Sri Gemawati; Musraini M. (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
Pappus theorem is  a  theorem that shows  collinearity of three points.  The three points are  the result of intersection lines  that  connects  any  six points. Any six points  are divided into  three points on a straight line and three points on another straight line. This paper  shows  that Pappus theorem  is  valid at  a  conic section  (ellips, parabola and hyperbola). The properties of  cross  ratio  are utilized to prove the validity of Pappus at the conic section.